Optimization of heavy metals chlorides resistance by Staphylococcus aureus andits ability to remove them - Radhi, Shamim (Iraqi Journal of Science, 2024)
Three Staphylococcus aureus isolates were selected after screening on nutrient agarmedia amended with 100μg/ml of five heavy metals chlorides (i.e: Aluminum Al+2, IronFe+2, Lead Pb+2, Mercury Hg+2 and Zinc Zn+2) from those isolates one S. aureus (S3) isolatewas selected depending on its resistance to all heavy metals chloride. Minimum inhibitoryconcentration (MIC) for this isolate was 1000μg/ml for all tested metals chlorides exceptHg+2 (300μg/ml). Growth of S. aureus (S3) was not affected in presence of pbCl2 and AlCl2for 72hrs; however, it was affected by ZnCl2 and FeCl2 during incubation period whilemercury causes no bacterial growth. In response to various temperatures bacterial isolatehad clear growth in presence of heavy metals ZnCl2, FeCl2, AlCl2, PbCl2at 28 ºC and 37 ºCand the growth was inhibited at 50 ºC in presence of FeCl2. At different pH values; 4, 7and 9 the growth of S. aureus (S3) isolate was affected at pH4 in presence of the fourheavy metals chlorides Al+2, Fe+2, Pb+2and Zn+2. S. aureus (S3) isolate showed the highestZn+2 removal ratio 43% while Pb+2 has the lowest removal ratio 7%.